From dizziness to severe ataxia and dysarthria: New cases of anti-Ca/ARHGAP26 autoantibody-associated cerebellar ataxia suggest a broad clinical spectrum - Wallwitz, Ulrike; Wildemann, Brigitte; Jarius, Sven; Hoffmann, Frank (Journal of neuroimmunology, 2017)
In 2010, a novel anti-neuronal autoantibody, termed anti-Ca, was described in a patient with subacute cerebellar ataxia, and Rho GTPase-activating protein 26 (ARHGAP26) was identified as the target antigen. Recently, three additional cases of anti-Ca-positive cerebellar ataxia have been published. In addition to ataxia, cognitive decline and depression have been observed in some patients. Here, we report two new cases of anti-Ca-associated autoimmune cerebellar ataxia. Patient 1 presented with dizziness and acute yet mild limb and gait ataxia. Symptoms stabilized with long-term oral corticosteroid therapy but transiently worsened when steroids were tapered. Interestingly, both initial occurrence and worsening of the patient's neurological symptoms after steroid withdrawal were accompanied by spontaneous cutaneous hematomas. Patient 2 initially presented with an increased startle response and myoclonic jerks, and subsequently developed severe limb and gait ataxia, dysarthria, oculomotor disturbances, head and voice tremor, dysphagia, cognitive symptoms and depression. Steroid treatment was started five years after disease onset. The symptoms then responded only poorly to corticosteroids. At most recent follow-up, 19 years after disease onset, the patient was wheelchair-bound. These cases extend the clinical spectrum associated with anti-ARHGAP26 autoimmunity and suggest that early treatment may be important in patients with this rare syndrome.